Influence of the spreading of roads on herbal vegetation composiition in the roads vicinity - Faltys, Vladimír; Bajer, Tomáš; Brunclík, Tomáš; Sákra, Tomáš; Chýlková, Jaromíra (Univerzita Pardubice, 2004)
The work deals with the impact of road salting materials (de-icing- salts) to vegetation composition close to roads. Very detailed qualitativeand quantitative botanical analysis of the herbaceous species composition has been investigated in the same sampling points as tin the preceding paper.